Desarrollo y validación de una técnica de inoculación a campo de Sclerotinia minor en el cultivo de maní - Rosso, Melina; Bressano, Marina; de Blas, Francisco; Oddino, Claudio; Soave, Sara; Giordano, Damián Francisco; Soave, Juan (Facultad de Ciencias Agropecuarias, 2021)
Sclerotinia minor causes peanut blight, a disease  hat generates losses to the crop. S. minor produces sclerotia as a resistance structure and is found in aggregate form in the field, making it  difficult to evaluate disease control tools. It is necessary to develop an inoculation technique  hat allows homogenizing the inoculum in each experimental unit. The objectives of this work were: to develop and validate a field inoculation methodology for S. minor in peanuts, and to evaluate the behavior of different genotypes of the crop. Sclerotia of S. minor were isolated and quantified from soil samples, subpopulations were selected and the inoculum was produced in two liquid culture media. The inoculum generated was applied in the field on ten peanut genotypes,  the intensity of the disease and the homogeneity of response were evaluated. The number of  sclerotia in soil was 0.81/100 g before and 2.07/100 g after inoculation. S. minor grew in both culture media, but potato dextrose agar broth presented greater advantages. The inoculation  technique was successful at achieving homogenous incidence values among repetitions.  Significant statistical differences were observed in the behavior of the genotypes towards the disease.